A novel warm-mix additive for SBR modified asphalt binder: Effects of Sasobit/epoxidized soybean oil compound on binder rheological and long-term aging performance. (1st December 2021) - Li, Qishi; Zhang, Henglong; Shi, Caijun; Chen, Zihao
Abstract: The thermal degradation of styrene-butadiene rubber (SBR) polymer during asphalt mixture preparation processes severely compromises the modifying effects of polymer on binder low-temperature performance. Sasobit/epoxidized soybean oil (Sasobit/ESO) compound has been demonstrated to be a promising warm-mix additive that can alleviate the negative short-term thermal aging influences on SBR modified asphalt binder (SBRMA) without compromising the original performance of binder itself. Nevertheless, there are few studies concerning the further investigation of in-service performance and long-term aging resistance of SBRMA modified by Sasobit/ESO compound. For wide application of this novel warm-mix additive, this study aims to investigate the influences of Sasobit/ESO on rheological performance and long-term aging resistance of SBRMA. The effects of this novel warm-mix additive on performance grade (PG) and aging resistances of SBRMA were assessed by dynamic shear rheometer (DSR), bending beam rheometer (BBR) or Fourier transform infrared spectroscopy (FTIR) tests. Meanwhile, the modifying mechanism of novel warm-mix additive was also explored from the perspective of chemical properties. The results indicate that Sasobit/ESO only makes a physical modification effect on SBRMA. Additionally, a decrease of 20 °C in preparation temperature was presented by warm-mix asphalt mixture in comparison with hot-mix mixture. The intermediate- and high-temperature PG of SBRMA were increased by two levels after the introduction of Sasobit/ESO whether in consideration of its warm-mix effect or not. Both short- and long-term aging resistances of SBRMA were improved with the introduction of Sasobit/ESO. More concretely, the short-term aging resistance of SBRMA was especially improved in consideration of its warm-mix effect, while the improved effect on long-term aging resistance was not further enhanced even if the warm-mix effect was accounted. Highlights: Sasobit/ESO can improve the anti-cracking ability of SBRMA before and after aging. Sasobit/ESO can enhance the high- and intermediate-temperature PG of SBRMA. Sasobit/ESO can improve the short- and long-term aging resistances of SBRMA.